Engaging publics in science: a practical typology - Heather Douglas; Megan K. Halpern; Eleanor Louson (Journal of Responsible Innovation)
Public engagement with science has become a prominent area of research and effort for democratizing science. In the fall of 2020, we held an online conference, Public Engagement with Science: Defining and Measuring Success, to address questions of how to do public engagement well. The conference was organized around conceptualizations of the publics engaged, with attendant epistemic, ethical, and political valences. We present here the typology of publics we used (volunteer, representative sample, stakeholder, and community publics), discuss the differences among those publics and what those differences mean for practice, and situate this typology within the existing work on public engagement with science. We then provide an overview of the essays published in this journal arising from the conference which provides a window into the rich work presented at the event.